Sizes and map positions of several plasmid-DNA-encoded transcripts in octopine-type crown gall tumors. - Gelvin, S B (1982)
The sizes and relative map positions of RNA molecules encoded by the plasmid DNA of several octopine-type tobacco crown gall tumors were determined by blot hybridization. At least six discrete polyadenylylated RNAs (sizes 0.73-1.75 kilobases) were detected in octopine-producing tumors (lines A6S/2, E9, and 15955/01). In one tumor (line 15955/1) in which octopine could not be detected, one of the RNA species was missing and another was diminished in abundance. Evidence is presented suggesting that the transcripts are encoded entirely by the plasmid DNA and do not originate from the surrounding plant DNA sequences.